Efektifitas Spiritual Emotional Freedom Technique Kombinasi Dzikir terhadap Penurunan Kejadian Insomnia pada Lanjut Usia - Sopian Halid; Irwan Hadi; Zulkahfi Zulkahfi; Baiq Nurainun Apriani Idris; Dian Istiana (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
The National Sleep Foundation America reports that 80% of erderly have trouble sleeping. Meeting the need for sleep rest in the elderly can be improved by teaching stimulating ways to motivate sleep. Spiritual Emotional Freedom Technique combined with dhikr therapy can calm the heart and can provide purity. The purpose of this study was to determine the effectiveness of the Spiritual Emotional Freedom Technique combination of dzikir to reduce the incidence of insomnia in the elderly. The design used in this study was a pre-experimental design with one group pre-test-posttest design approach. The sample in this study amounted to 64 people using the total sampling technique. The independent variable is the Spiritual Emotional Freedom Technique Combination of Dhikr and the dependent variable is the decrease in the incidence of insomnia. The research instrument used a checklist observation sheet using construct validity and then analyzed using the Mc Nemar test. Based on the results of the Mc test. The Nemar test with a level of error (α) = 0.05 obtained a value of p = 0.000 (p <α), which means that there is a significant effect of the application of the Spiritual Emotional Freedom Technique Combination of Dzikir on the decrease in the incidence of insomnia in the elderly.